Analysis of Accountability and Transparency of Financial Management in Teluk Nayang Village, Pujud District, Rokan Hilir Regency - Anita Anita; Siska Siska (Budapest International Research and Critics University, 2022)
The purpose of this study is to examine the Accountability and Transparency of Village Fund Allocation Management in Teluk Nayang Village, Pujud District, Rokan Hilir Regency, which includes planning, implementation, administration, and reporting. This study employed a qualitative descriptive methodology. In-depth interviews, observations, and document studies were used to collect data, which was then analyzed utilizing an interactive analytical model in three stages: data reduction, data presentation, and conclusion. This study indicates that the Teluk Nayang Village Fund Allocation management has implemented the principle of accountability which Transparency, Participation, and Responsiveness support. To realize transparency in the direction of Village Fund Allocations, Teluk Nayang Village provides information to the community through village meetings and the installation of billboards containing information on Village Fund Allocations for each program design implemented by the VillageVillage. The Teluk Nayang Village Fund Allocation Report has also implemented the principles and principles of accountability that have been fully implemented for the physical and comprehensive Accountability of the Village Fund Allocation, as evidenced by the Village Financial Report realized by the APBDesa. However, there are obstacles faced in the form of delays in incoming funds from the center to the VillageVillage and the problem of human resources who have limitations in operating the financial system or village computerization that affect performance in the government of Teluk Nayang Village.